Why media representations of corporations matter for public health policy: a scoping review - Heide Weishaar; Lori Dorfman; Nicholas Freudenberg; Benjamin Hawkins; Katherine Smith; Oliver Razum; Shona Hilton (BMC, 2016)
Abstract Background Media representations play a crucial role in informing public and policy opinions about the causes of, and solutions to, ill-health. This paper reviews studies analysing media coverage of non-communicable disease (NCD) debates, focusing on how the industries marketing commodities that increase NCD risk are represented. Methods A scoping review identified 61 studies providing information on media representations of NCD risks, NCD policies and tobacco, alcohol, processed food and soft drinks industries. The data were narratively synthesized to describe the sample, media depictions of industries, and corporate and public health attempts to frame the media debates. Results The findings indicate that: (i) the limited research that has been undertaken is dominated by a focus on tobacco; (ii) comparative research across industries/risk-factors is particularly lacking; and (iii) coverage tends to be dominated by two contrasting frames and focuses either on individual responsibilities ('market justice' frames, often promoted by commercial stakeholders) or on the need for population-level interventions ('social justice' frames, frequently advanced by public health advocates). Conclusions Establishing the underlying frameworks is crucial for the analysis of media representation of corporations, as they reflect the strategies that respective actors use to influence public health debates and decision making. The potential utility of media research lies in the insights that it can provide for public health policy advocates about successful framing of public health messages and strategies to counter frames that undermine public health goals. A better understanding of current media debates is of paramount importance to improving global health.